The English coinages of William I (1066-1087) and William II (1087-1100) and their implications for our understanding and the public representation of the early Norman period - Thompson-Rohde, Anja Christina Friedel (2020)
This multi-disciplinary project brings together the largest dataset of the surviving English coins of William the Conqueror and William Rufus yet collated. The dataset focuses on those coins which are held in public collections, thus creating a particular and specific base from which to examine not just the information held within the coins but also their contribution to museological questions. It examines these data using numismatic and statistical methods, interprets those findings from the standpoints of economic, social, and personal history, and investigates how the resulting stories can be effectively used in the UK heritage industry to engage wide audiences, and to affect the public representation of Early Norman England. The project outcomes are therefore twofold: It identifies new narratives which deepen and add nuance to our understanding of the period, and provides indisputable evidence of the value of public numismatic collections to the aims and purposes of museums in 21st century British society.